Integrated STORET–System Dynamics Approach for Pollution Control and Assimilation Capacity Management in a Small Urban Lake: A Case Study of Situ Tlajung Hilir, Bogor Regency, Indonesia - Syamsul; Rosadi Rosadi; Sata Yoshida Srie Rahayu (Indonesian Journal of Applied Environmental Studies, 2026)
Small urban lakes are increasingly threatened by domestic and industrial wastewater inputs that exceed their natural assimilation capacity. This study aimed to evaluate the water quality status and develop a dynamic pollution control model for Situ Tlajung Hilir, Bogor Regency, Indonesia. Water quality was assessed using the STORET method based on Government Regulation No. 22/2021 standards, while pollution dynamics were simulated using a system dynamics model consisting of population growth, domestic load, industrial load, and assimilation capacity submodels. Historical monitoring data (2019–2023) were used for calibration and behavioral validation through trend comparison. The lake was classified as heavily polluted, with BOD, Total Nitrogen, and Total Phosphate exceeding permissible limits and surpassing assimilation capacity. Simulation of management scenarios (2020–2035) showed that business-as-usual conditions lead to continuous degradation, whereas integrated domestic and industrial wastewater treatment can reduce pollutant loads by 60–80% and gradually approach ecological balance. The proposed integrated STORET–system dynamics framework provides a practical decision-support tool for sustainable lake restoration and urban water resource management.